Modulatory effects of traditional Chinese medicines on gut microbiota and the microbiota-gut-x axis - Luo, Tingting; Che, Qingya; Guo, Ziyi; Song, Tingxia; Zhao, Juanjuan; Xu, Delin (Frontiers in Pharmacology, 2024)
Abstract：The gut microbiota offers numerous benefits to the human body, including the promotion of nutrient absorption, participation in metabolic processes, and enhancement of immune function. Recent studies have introduced the concept of the gut-organ axis, which encompasses interactions such as the gut-brain axis, gut-liver axis, and gut-lung axis. This concept underscores the complex interplay between gut microbiota and various organs and tissues, including the brain, heart, lungs, liver, kidneys, muscles, and bones. Growing evidence indicates that gut microbiota can influence the onset and progression of multi-organ system diseases through their effects on the gut-organ axis. Traditional Chinese medicine has demonstrated significant efficacy in regulating the gastrointestinal system, leveraging its unique advantages. Considerable advancements have been made in understanding the role of gut microbiota and the gut-organ axis within the mechanisms of action of traditional Chinese medicine. This review aims to elucidate the roles of gut microbiota and the gut-organ axis in human health, explore the potential connections between traditional Chinese medicine and gut microbiota, and examine the therapeutic effects of traditional Chinese medicine on the microbiota-gut-organ axis. Furthermore, the review addresses the limitations and challenges present in current research while proposing potential directions for future investigations in this area.